Enhancing passenger statisfaction in Kedah Public Bus Services : A comprehensive analysis of sevices quality dimensions and accessibility - Nur Amirah, Muhayadin (2024)
The purpose of this study was to investigate the current state of public bus transportation in Kedah, focusing on the factors influencing customer satisfaction and the decline in demand for bus services. The problem statement revolves around the decrease in demand for public bus has caused low demand for public bus service in Kedah and traffic congestion. The service quality (SERVQUAL) model theory and the Concept of Access are used as the main variables, namely reliability, assurance, tangibles, empathy, responsiveness, accessibility, and customer satisfaction in the context of public bus transportation in Kedah. This research paper utilizes a quantitative research design with hypotheses testing to explore the relationships between predetermined variables. Data collection involves closed-ended questionnaires administered to a sample size of 388 passengers selected through multistage sampling, incorporating both cluster and convenience sampling techniques to ensure geographic representation and route-specific diversity. The analysis conducted using PLS-SEM managed to answer the research objectives and questions of this research paper in which it revealed strong positive relationships between reliability, responsiveness, accessibility, and customer satisfaction, indicating that improvements in these areas can lead to higher levels of satisfaction among passengers. However, assurance, tangibles, and empathy did not show significant effects on customer satisfaction. Despite limitations, the research paper provides theoretical contributions and practical implications for bus operators and government authorities. In conclusion, improvements in transportation sector need to be taken so that public bus transport operations become more efficient and satisfaction among users will also increase